Spray-dried Ancellotta red wine: natural colorant with potential for food applications - Alvarez Gaona, Izmari Jasel (2019)
Ancellotta red wine (Vitis vinifera L.) was encapsulated by spray-drying (inlet and outlet temperatures were 145 °C and 70 °C, respectively) to obtain a wine powder with a low water activity (aw) using maltodextrin DE10 as an encapsulating agent. The retention of total monomeric anthocyanins (TMA) in the wine powder was found to be greater than 80%. Anthocyanin profiles of Ancellotta liquid wine and wine powder were characterized by using HPLC–DAD and 33 compounds were identified. The wine powder was stored under two different water activity values (aw 0.25 and aw 0.33). Furthermore, the TMA (pH-differential method), total anthocyanins and malvidin-3-glucoside were determined by HPLC–DAD for up to 90 days’ storage at 38 °C. Total anthocyanins and malvidin-3-glucoside decreased very slowly during storage. The stability of anthocyanins and color differences (ΔE*ab) in 1% wine powder solution at different pHs and temperatures were evaluated. These results indicated that Ancellotta wine powder has the potential to be used as a food colorant in low pH and low water activity foods.